Analytical and Textual Study of the novel Seratushuja b Bakseer: دراسة فنية و تحليلية لرواية تاريخية "سيرة الشجاع" لعلي أحمد باكثير - Javeria, Javeria; Parveen, Dr. Azra (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
In Arabic literature, Bakseer’s figure is quite unique and well known.Particularly when we talk about historical novel,Bakseer is regarded as the pioneer of this genre. “Seeratush-Shujaa” is his typical historical novel which gives a graphic picture of the period of Al Aazid Billah the last ruler of Fatmic dynasty.The conspiracies of the royal court, along with the allied acts of treachery have been depicted in detail.This novl especially focuses on the differences and clashes between the two prominent ministers Shawer and Zargham.Both of them were real persons. Zargham killed Shawer’s two sons,but speared his third son Shujaa mainly for his bravery and honesty.Later on, Shujaa also started loving Zargham with the passage of time.Shawer fled to Noor-ud-Din Zangi and convinced him to help him. Zangi sent Asad-ud-Din Shairkooh and Slahudddin Ayobi to Egypt to help Shawer who ultimately succeeded in killing Zargham.Subsequently, Shawer regained ministry and Aazid became a puppet in his hands.All the affairs of the caliphate were supervised by Shawer.Taking advantage of his position,he developed friendly relation with the English-back King Maree, and hence became a traitor to his own country.He handed over Fustat and some other cities to Maree.As a result,his son Shuja started hating him and decided to support Asad-ud-Din and Slahuddin. The hero of the novel is Shjaa,who opposes his father and supports the truth.One day Shawer invited Asad-ud-Din and his army to a party and asked his new slave Yaqoot to poison the food to be served to Asad-ud-Din and Slahuddin.Shujaa’s wife Sumaiya overheard this conversation and informed Shujaa of the plot who consequently got annoyed.He exchanged hot words with his father and revealed that he knew all his evil [1]designs.this irritated Shawer and he ordered his slave Yaqoot to murder Shujaa.Before his death,Shuja expressed two wishes:one that Asad-ud-Din should forgive his father Shawer so that the latter might repent of his sins; the second that his son who has not yet born should be given the name “Zargham” and title “Asad-ud-Din”. The beauty of the novel lies in the writer’s skill of blending the romantic and the real.The diction is quite impressive and fully charged.Metaphors,Similes and references have been used dexterously.Dialogues are charged with sublime emotions and, as such,touch the chords of the heart.